Spines slow down dendritic chloride diffusion and affect short-term ionic plasticity of GABAergic inhibition - Mohapatra, Namrata; Tønnesen, Jan; Vlachos, Andreas; Kuner, Thomas; Deller, Thomas; Nägerl, U. Valentin; Santamaria, Fidel; Jedlicka, Peter (Scientific reports, 2016)
Cl− plays a crucial role in neuronal function and synaptic inhibition. However, the impact of neuronal morphology on the diffusion and redistribution of intracellular Cl− is not well understood. The role of spines in Cl− diffusion along dendritic trees has not been addressed so far. Because measuring fast and spatially restricted Cl− changes within dendrites is not yet technically possible, we used computational approaches to predict the effects of spines on Cl− dynamics in morphologically complex dendrites. In all morphologies tested, including dendrites imaged by super-resolution STED microscopy in live brain tissue, spines slowed down longitudinal Cl− diffusion along dendrites. This effect was robust and could be observed in both deterministic as well as stochastic simulations. Cl− extrusion altered Cl− diffusion to a much lesser extent than the presence of spines. The spine-dependent slowing of Cl− diffusion affected the amount and spatial spread of changes in the GABA reversal potential thereby altering homosynaptic as well as heterosynaptic short-term ionic plasticity at GABAergic synapses in dendrites. Altogether, our results suggest a fundamental role of dendritic spines in shaping Cl− diffusion, which could be of relevance in the context of pathological conditions where spine densities and neural excitability are perturbed.
Gesehen am 10.07.2020